Pengembangan Kecamatan di Kabupaten Bandung Barat - Dewi Kurniasih; Yudi Rusfiana (Department of Government Studies Universitas Muhammadiyah Makassar, 2016)
One of device regency is the subdistrict. Subdistrict as the technical regional programs, have work areas, led by Camat. When society still do not feel any equitable development results, it was natural to enter the 10 years, the West Bandung Regency Government planning subdistrict development strategy. The population is increasing, the sub-district government services should be improved. Geographical constraints and demands of society into its own problems in terms of a sub-district development. Subdistricts development is intended to increase the capacity of districts, especially in governance, development and public service. The purpose of this study is the recommendation several strategies development, especially in Lembang Subdistrict, Cipatat and Cipongkor in West Bandung Regency. The method used is descriptive method with qualitative approach through surveys. Data was collected through library research, observation and interviews. The results showed that all three subdistricts have met the basic requirements, technical and administrative measures to be developed. This is in accordance with the mandate of Government Regulation No. 19 Year 2008 regarding the District is still valid. Salah satu perangkat daerah kabupaten adalah kecamatan. Kecamatan sebagai pelaksana teknis kewilayahan, mempunyai wilayah kerja yang dipimpin oleh Camat. Ketika masyarakat belum merasakan adanya pemerataan hasil pembangunan, maka wajarlah memasuki 10 tahun, Pemerintah Kabupaten Bandung Barat merencanakan strategi pengembangan kecamatan. Jumlah penduduk semakin bertambah maka pelayanan pemerintah kecamatan harus ditingkatkan. Kendala geografis dan tuntutan masyarakat menjadi permasalahan sendiri dalam sebuah pengembangan kecamatan. Pengembangan kecamatan ditujukan untuk meningkatkan kapasitas kecamatan terutama dalam penyelenggaraan pemerintahan, pembangunan dan pelayanan publik. Tujuan penelitian ini adalah terekomendasinya beberapa strategi pengembangan khususnya pada Kecamatan Lembang, Cipatat dan Cipongkor di Kabupaten Bandung Barat. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif melalui survei. Teknik pengumpulan data dilakukan dengan studi pustaka, observasi dan wawancara. Hasil penelitian menunjukkan bahwa ketiga kecamatan tersebut telah memenuhi persyaratan dasar, teknis dan administratif untuk dikembangkan. Hal ini sesuai dengan amanah Peraturan Pemerintah No. 19 Tahun 2008 tentang Kecamatan yang masih berlaku.